Digital financial inclusion and economic green growth: evidence from counties covered by China’s national key ecological functional zones - Mo, Li; Chen, Song; Wan, Shenwei; Liang, Chen; Ma, Ye (Frontiers in Environmental Science, 2025)
Against the backdrop of growing attention being paid to both ecological compensation and the digital economy, this paper explores the impact of digital financial inclusion on green economic growth in counties within China’s National Key Ecological Functional Zones (NKEFZs) from 2014 to 2022, using panel data from 393 counties. Employing a two-way fixed-effects model, the study finds that digital financial inclusion promotes both traditional and green economic growth. The study results are robust, even after a series of robustness tests. The mechanisms identified include agricultural technology progress, industrial structure upgrading, and enterprise innovation and entrepreneurship. However, the effect is less significant in western and northeastern regions, as well as in windbreak and sand-fixing zones. The study highlights the potential of digital finance to help resource-rich, underdeveloped regions overcome the “resource curse” and foster sustainable economic growth.